Prenatal fluoxetine impairs non-hippocampal but not hippocampal memory in adult male rat offspring. (1st October 2021) - Moraga-Amaro, Rodrigo; Díaz-Galarce, Raul; Donoso-Ramos, Juan P.; Ugalde, Valentina; Linsambarth, Sergio; Doorduin, Janine; de Vries, Erik FJ.; Ampuero, Estibaliz; Peña, Francisca; Pacheco, Rodrigo; Wyneken, Ursula; Stehberg, Jimmy
Abstract: Fluoxetine is often prescribed to treat depression during pregnancy. Rodent studies have shown that fluoxetine exposure during early development can induce persistent changes in the emotional behavior of the offspring. However, the effects of prenatal fluoxetine on memory have not been elucidated. This study evaluates the memory of adult male offspring from rat dams orally administered with a clinically relevant dose of 0.7 mg/kg fluoxetine from 9 weeks before pregnancy to 1 week before delivery. Hippocampal-dependent (Morris Water Maze, MWM) and non-hippocampal-dependent (Novel Object Recognition, NOR) memory paradigms were assessed. Anxiety- and depressive-like symptoms were also evaluated using the Open Field Test, Tail Suspension Test and Sucrose Preference Test. Male rats exposed to fluoxetine during gestation displayed NOR memory impairments during adulthood, as well as increased anxiety- and depressive-like symptoms. In the MWM, the offspring of fluoxetine-treated dams did not show learning deficits. However, a retention impairment was found on remote memory, 15 days after the end of training. Molecular analyses showed increased expression of NMDA subunit NR2B, and a decrease in NR2A -to- NR2B ratio in the temporal cortex, but not in the hippocampus, suggesting changes in NMDA receptor composition. These results suggest that in utero exposure to fluoxetine induces detrimental effects on non-hippocampal memory and in remote retention of hippocampal-dependent memory, which is believed to be stored in the temporal cortex, possibly due to changes in cortical NMDA receptor subunit stoichiometry. The present results warrant the need for studies on potential remote memory deficits in human offspring exposed to fluoxetine in utero . Highlights: Gestational exposure to fluoxetine induced increased anxiety- and depressive-like symptoms during adulthood. Gestational exposure to fluoxetine induced impairments in non-hippocampal dependent novel object recognition memory. Gestational fluoxetine induced impairments in remote memory retention but not in learning & long-term spatial memory. Prenatal fluoxetine did not affect expression of AMPAR & NMDAR subunits GluA1, GluA2 & NR2A in hippocampus or temporal cortex. Gestational fluoxetine increased NMDAR NR2B /NR2A subunit stoichiometry in temporal cortex, but not hippocampus.